The Status of the Marine Economy in South Africa Forward to Sustainable Development and Implications for Vietnam’s Maritime Strategy - Trang Mai Tran (Journal of Research in Environmental and Science Education, 2025)
The marine economy is a vital component of South Africa’s overall economic framework, encompassing a broad range of industries such as fishing, shipping, offshore oil and gas, marine tourism, and aquaculture. Surrounded by extensive coastlines, South Africa is strategically positioned with a vast maritime zone that presents considerable potential for economic expansion. Harnessing this potential through the development of the marine economy is crucial for the nation’s sustainable economic growth. This paper aims to provide an in-depth analysis of the current state of South Africa’s marine economy by examining the performance of its key sectors. It evaluates both the challenges and opportunities faced by the industry, while also discussing the government’s policies and strategies designed to foster sustainable development. One of the key objectives is to shed light on the significant contributions of the marine economy to the national economy, offering a comprehensive understanding of its role and importance. Additionally, the paper will highlight the necessary steps for unlocking the full economic potential of South Africa’s maritime resources. The marine economy not only promises to boost economic output but also to create job opportunities and enhance the nation’s competitiveness on the global stage. By addressing the existing obstacles and exploring innovative solutions, South Africa can build a resilient and thriving marine sector that will contribute to the long-term prosperity of the country.